Five Methods Comparison of 10 Years Cardiovascular Disease Risk Estimation in the Community in Sleman-Yogyakarta - Clarentia Dwivani; Herlina Herlina; Karina Harijadi; Budianto Budianto; Rita Suhadi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Cardiovascular disease is the highest cause of death with total of 17.5 million deaths in the world. Nowadays there have beenexists many methods to calculate the risk of cardiovascular disease within the next 10 years, 5 of them are Framingham Risk Score (FRS) BMI and Cholesterol, Pooled Cohort Equations (PCE), CV Risk Calculator, and Systematic Coronary Risk Evaluation (SCORE). The aim of this study waiss to compare the 5 methods of 10-year risk of cardiovascular disease based on mean values, risk categories, and statin recommendation. This observational analytic study was done with cross-sectional design. There were 169 respondents in Sleman, Yogyakarta who participated to this study. Normality of risk measurement data was performed using Kolmogorov-Smirnov test and comparative test was performed using Repeated ANOVA. Both proportion of risk categorization and statin therapy was calculated using the Marginal Homogeneity test. The average risk of  FRS (BMI and Cholesterol), PCE, CV Risk Calculator, and SCORE were 14,6±11,7% (medium risk), 13,3±11,3% (medium risk), 6,8±6,4% (medium risk), 6,8±6,4% (medium risk), and 2,6±3,5% (medium risk).  There were significant differences from the comparison between among methods on mean values and risk categories (p <0.01), except on PCE with FRS BMI (p=0.11) and PCE with CVRiskcalculator (p = 1.00). Comparison of statin therapy recommendation among FRS Cholesterol with PCE, FRS Cholesterol with SCORE, and PCE with FRS BMI methods showed significant differences (p <0.01), whereas FRS Cholesterol with FRS BMI and PCE with SCORE were not significantly different (p = 0,06 and p = 0,05).